1997
DOI: 10.1093/clinids/24.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Reactions in U.S. Marine Corps Personnel Who Received Japanese Encephalitis Vaccine

Abstract: The overall hypersensitivity reaction rate among 14,249 U.S. Marine Corps personnel who received 36,850 doses of an investigational Japanese encephalitis vaccine was 10.3 per 10,000 doses; reaction rates were 16.1 and 10.3 per 10,000 doses for the first two doses, and 2.0 per 10,000 doses for the third. The reaction rate was 26.7 per 10,000 vaccinees. Of 38 reactors, 26 had urticaria and/or angioedema, and 11 had pruritus. Vaccine reaction intervals clustered within 48 hours for dose 1, but the median reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…4,5,8,19 Although it has been greatly improved through ultracentrifugation, the vaccine contains components, such as gelatin, which may play a role in hypersensitivity adverse reactions. 20 The relationship between vaccination and orbital swelling reported by two subjects in this study is difficult to evaluate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,8,19 Although it has been greatly improved through ultracentrifugation, the vaccine contains components, such as gelatin, which may play a role in hypersensitivity adverse reactions. 20 The relationship between vaccination and orbital swelling reported by two subjects in this study is difficult to evaluate.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 An additional 10,000 doses subsequently were administered under this IND to U.S. military personnel deploying to the region for training exercises and to Ͼ 35,000 Navy personnel and dependents after an outbreak in Okinawa. 8,9 Although a two-dose primary series protected native populations in studies in Taiwan and Thailand, the vaccine appeared to be less immunogenic in immunologically naive recipients. 7,[9][10][11][12] Practically all recipients, however, responded well to a third dose given either as a part of the primary series (1-2 weeks after the second injection, or as a booster (6-12 months after the initial series).…”
mentioning
confidence: 99%
“…Higher rates of AEs were found in Denmark; the rate of allergic mucocutaneous reactions was 73/350,000 doses and rate of any AEs was 101/350,000 doses) [40]. Other studies have found that while local, mild reactions are common, low rates of serious adverse events occur, though few have had sufficient sample sizes and follow up times to detect rare neurological events [31,38,41,42,46,[48][49][50][51][52][53]. Overall rates of local reactions has been estimated around 20%, mild systemic at 10-30%, hypersensitivity at 1-64/10 000 and acute encephalitis at 1/75 000 to 1/ million doses [1].…”
Section: Adverse Events and Toxicitymentioning
confidence: 99%
“…Symptoms and signs of these 10 cases ranged from headaches, difficulty in concentrating, paraesthesia, parkinsonian gait, and myelitis [57]. Risk factors for hypersensitivity include history of allergy (including asthma, hayfever, rhinitis, nickel sensitivity), young age, female sex [36,41]. Other risk factors for adverse events could include alcohol consumption in the 9 days prior to (but not on the day of) JE vaccination [45].…”
Section: Adverse Events and Toxicitymentioning
confidence: 99%
“…It may be postulated that a history of allergic disorders could be a risk factor for developing adverse events following immunization (AEFI) with live JE vaccine. It is possible that many of the adverse events are due to allergy to gelatin, the stabilizer used in the vaccine rather than to the vaccine itself [13,14].…”
Section: Risk Factors For Development Of Adverse Eventsmentioning
confidence: 99%